Compact Power Divider Integrated with Coupler and Microstrip Cavity Filter for X-band Surveillance Radar System - Yudi Yuliyus Maulana; Yussi Perdana Saputera; Arief Budi Santiko; Arie Setiawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper present the compact power divider integrated with coupler and microstrip cavity filter for x-band surveillance radar system. These modules consist of several devices (splitter, filter and coupler) it is integrated in a single module aims to reduce the loss in the joint connectors. The bandpass filter is use microstrip cavity filter for operating on X-Band Frequency and deployed on RT/duroid 5880. The power divider and coupler is designed using quarter wavelength transformer. A theoretical analytical circuit model will be presented, from the theoretical model, a compact integrated module will be designed and simulated. The proposed compact integrated module is small in dimension and performs a compact size. The compact integrated devices design on X-Band frequency is simulated and the result is presented.